El juego y la motricidad gruesa en los niños de 4 a 5 años de la escuela fiscomisional Tcrn.Lauro Guerrero ubicada en la ciudad de loja, en el período 2019-2020. - González Poma, Dayanna Katherine (2021)
The present investigation called: The game and the gross motor skills in children of 4 to 5 years in the Fiscomicional School Tcrn. Lauro Guerrero located in Loja city, in the period 2019-2020, it had like objective to analyze the importance of games in gross motor skills, in children from 4 to 5 years old. The design was non-experimental, with a mixed focus and descriptive scope, for which the following methods were used: analytical-synthetic, scientific and inductive-deductive; in addition a descriptive statistic was used, likewise, to get information, the interview technique was used, which was applied to the teacher and the Nelson Ortiz Abbreviated Development Scale (EAD-1) was used as an instrument, which allowed to diagnose the development of gross motor skills, in a group of 19 children. Nonprobability sampling was taken into account, which is a technique where a specific sample was selected. The results that were obtained are that 31,58% of the children were in a medium-high level and 68,42% of the children were in a medium level, showing problems such as: bouncing and catching the ball, jumping with feet together, alternating feet, three or more steps on a single foot, high jumps.In view of the evidenced problems, a proposal called "playing, playing my motor skills I'm improving" wapa elaborated, which is constituted by different types of games, with the objetive of strengthening gross motor skills in children so that learning is more entertaining and meaningful, promoting their autonomy and control of the body to improve the development. Therefore, it is recommended that children require more activities and approaches that allow them to develop 100% of their gross motor skills together with the help of teachers.